Some Non-Local Logistic Population Model with Non-Zero Boundary Condition - Ubilla-Lopez, P; Cerda-Loyola, P (World Scientific Publishing Co. Pte Ltd, 2018)
In this paper, we study some type of equations which may model the behavior of species inhabiting in some habitat. For our purpose, using a priori bounded techniques, we obtain a positive solution to a family of non-local partial differential equations with non-homogeneous boundary conditions. © 2018 World Scientific Publishing Company.